Replication of restless legs syndrome loci in three European populations. Issue 5 (10th March 2009) - Kemlink, D; Polo, O; Frauscher, B; Gschliesser, V; Högl, B; Poewe, W; Vodicka, P; Vavrova, J; Sonka, K; Nevsimalova, S; Schormair, B; Lichtner, P; et al.
Abstract : Background: Restless legs syndrome (RLS) is associated with common variants in three intronic and intergenic regions in MEIS1, BTBD9, and MAP2K5/LBXCOR1 on chromosomes 2p, 6p and 15q. Methods: Our study investigated these variants in 649 RLS patients and 1230 controls from the Czech Republic (290 cases and 450 controls), Austria (269 cases and 611 controls) and Finland (90 cases and 169 controls). Ten single nucleotide polymorphisms (SNPs) within the three genomic regions were selected according to the results of previous genome-wide scans. Samples were genotyped using Sequenom platforms. Results: We replicated associations for all loci in the combined samples set (rs2300478 in MEIS1, p = 1.26×10 −5, odds ratio (OR) = 1.47, rs3923809 in BTBD9, p = 4.11×10 −5, OR = 1.58 and rs6494696 in MAP2K5/LBXCOR1, p = 0.04764, OR = 1.27). Analysing only familial cases against all controls, all three loci were significantly associated. Using sporadic cases only, we could confirm the association only with BTBD9 . Conclusion: Our study shows that variants in these three loci confer consistent disease risks in patients of European descent. Among the known loci, BTBD9 seems to be the most consistent in its effect on RLS across populations and is also most independent of familial clustering.